1993
DOI: 10.1159/000204379
|View full text |Cite
|
Sign up to set email alerts
|

Interferon plus Glucocorticoids as Intensified Maintenance Therapy Prolongs Tumor Control in Relapsed Myeloma

Abstract: Interferon-α-2b (IFN) has been demonstrated to prolong remission duration and survival in responding multiple myeloma (MM) patients. The aim of this study was to intensify maintenance therapy adding glucocorticoids (GLU) to the standard IFN therapy. Twenty-eight relapsed MMs with stable disease or response after conventional chemotherapy received IFN + GLU. The treatment included 3 megaunits of IFN 3 times a week continuously until relapse, plus 4 days pulsed high-dose dexamethasone (40 mg/day for 4 days every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…31 Two recent studies suggested that the combination of interferon and glucocorticoids were effective as maintenance therapy for myeloma patients. 19,20 Since maintenance interferon does not improve outcome, this benefit may be observed with the use of glucocorticoids alone. Although pulse dexamethasone produced a similar outcome to 3-times-a-week interferon maintenance therapy among patients responding to MD induction therapy, 21 the type and length of induction therapy (melphalan-containing compared with VAD-like regimens) and the type, dose, and schedule of steroids may be critical to their efficacy during maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Two recent studies suggested that the combination of interferon and glucocorticoids were effective as maintenance therapy for myeloma patients. 19,20 Since maintenance interferon does not improve outcome, this benefit may be observed with the use of glucocorticoids alone. Although pulse dexamethasone produced a similar outcome to 3-times-a-week interferon maintenance therapy among patients responding to MD induction therapy, 21 the type and length of induction therapy (melphalan-containing compared with VAD-like regimens) and the type, dose, and schedule of steroids may be critical to their efficacy during maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] For patients either responding or showing stable disease following conventional chemotherapy, a single-arm study demonstrated that maintenance therapy with oral prednisone (50 mg 3 times per week) and interferon resulted in a long duration of remission and overall survival. 19 In a Southwest Oncology Group (SWOG) study, 89 patients responding to induction vincristine, doxorubicin, and dexamethasone (VAD) chemotherapy were randomized to receive maintenance therapy with either maintenance prednisone (50 mg 3 times per week with interferon or interferon alone). 20 Progression-free survival was increased from 9 to 19 months for patients given the combination compared with patients given interferon alone.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have shown encouraging results with a combination of IFN-a and glucocorticoids given as maintenance therapy (84,85). A recently published SWOG trial suggests that 50 mg alternate-day prednisone could improve survival in patients responding to induction chemotherapy (86).…”
Section: Maintenance Therapymentioning
confidence: 99%
“…Alpha-interferon (IFN-a) has been successfully em ployed in the treatment of several hematologic malignan cies such as hairy cell leukemia (HCL) [1,2], chronic myeloid leukemia (CML) [3], non-Hodgkin's lymphoma (NHL) [4], essential thrombocythemia (ET) [5] and multi ple myeloma (MM) [6,7], while other indications are under investigation [8]. IFN-a therapy can cause long term side effects such as autoimmune thyroid dysfunc tions, development of other autoimmune diseases and the isolated appearance of autoantibodies.…”
Section: Introductionmentioning
confidence: 99%